Determination of Lifestyle Factors on the Incidence of Hypertension in Peri Urban Areas - Dandi Oka Subantara; Yeli Yulianti; Latif Hisbulloh; M.Luthfi Adillah (FORIKES, 2026)
Hypertension cases in developing countries, including Indonesia, continue to rise annually, with a particularly high burden in densely populated provinces such as West Java. If left unmanaged, hypertension may progress to severe complications that threaten individual health and quality of life. Identifying lifestyle-related determinants that significantly contribute to hypertension is essential so that individuals can modify behaviors that increase their risk. This study aimed to analyze the lifestyle factors most strongly associated with the incidence of hypertension among residents living in a peri urban area. A descriptive–correlative design with an analytical cross sectional approach was employed. The study involved 434 respondents diagnosed with hypertension and residing in a peri urban region, specifically Mangkubumi District, located at the administrative border between the regency and the city. Variables assessed included sodium intake, physical activity, stress level, obesity status, and smoking history. Statistical analysis was conducted to determine the relationship between each lifestyle factor and hypertension incidence. The findings revealed that sodium (salt) intake and low levels of physical activity were significantly associated with hypertension (p < 0.05). Conversely, stress level, obesity, and smoking history did not show significant relationships, as indicated by p values above 0.05. Among all variables, physical activity demonstrated the strongest association with hypertension, with a p value of 0.021. In conclusion, lifestyle factors, particularly physical activity and sodium intake, play a significant role in the occurrence of hypertension in peri urban communities. These results underscore the importance of promoting healthier lifestyle behaviors to prevent complications related to hypertension. Keywords: risk factors; lifestyle; peri urban; hypertension